Cloning, expression and protective capacity of 37 kDa outer membrane protein gene (ompH) of Pasteurella multocida serotype B:2 - Tan, H.Y.; Nagoor, N.H.; Sekaran, S.D. (2010)
The major outer membrane protein (OmpH) of 4 local Malaysian strains of Pasteurella multocida serotype B:2 were characterized in comparison to ATCC strains. Three major peptide bands of MW 26, 32 and 37 kDa were characterized using SDS-PAGE. Two of these fragments, the 32 kDa and 37 kDa were observed to be more reactive with a mouse polyclonal antiserum in all of the local isolates as well as the ATCC strains in a Western blot. However, the 32 kDa fragment was found to cross react with other Gram negative bacteria. Therefore, the 37 kDa OmpH was selected as vaccine candidate. The 37 kDa ompH gene of the isolated strain 1710 was cloned into an Escherichia coil expression vector to produce large amounts of recombinant OmpH (rOmpH). The 37 kDa ompH gene of strain 1710 was sequenced. In comparison to a reference strain X-73 of the ompH of R multocida, 39bp was found deleted in the 37 kDa ompH gene. However, the deletion did not shift the reading frame or change the amino acid sequence. The rOmpH was used in a mice protection study. Mice immunized and challenged intraperitoneally resulted 100 protection against P. multocida whilst mice immunized subcutaneously and challenged intraperitoneally only resulted 80 protection. The rOmpH is therefore a suitable candidate for vaccination field studies. The same rOmpH was also used to develop a potential diagnostic kit in an ELISA format.